Interplay of Backbone Conformation, Morphology and Thermoelectric Properties of Benzodifuranone‐Isatin Acceptor Polymers - Hinojosa, Diego R.; Pataki, Nathan J.; Pallini, Francesca; Freychet, Guillaume; Erhardt, Andreas; Schuller, Kevin; Olthof, Selina; Meerholz, Klaus; McNeill, Christopher R.; Caironi, Mario; Günther, Florian [UNESP]; Sommer, Michael (Wiley, 2025)
Abstract Benzodifuranone (BDF)‐isatin‐based conjugated acceptor copolymers with different stereoelectronic properties are designed, guided by density functional theory calculations. syn ‐ and anti ‐conformations are predicted to depend on both the presence of chlorine substituents as well as on the steric demand of the comonomer. Backbone torsion decreases with the comonomer of the order thiophene (T) > furan (F) > acetylene (A). Six copolymers of BDF‐isatin with T, F, and A are prepared, referred to as H‐BDF‐T, Cl‐BDF‐T, H‐BDF‐F, Cl‐BDF‐F, H‐BDF‐A, and Cl‐BDF‐A. Electrochemically and spectroscopically determined HOMO and LUMO energy levels align qualitatively and confirm a stabilization of the LUMO of the chlorinated copolymers. The thin film microstructures of H‐BDF‐A and Cl‐BDF‐A, having a linear backbone, are characterized by an edge‐on orientation, while the four remaining copolymers with a more curved backbone predominantly orient face‐on. The non‐chlorinated furan copolymer H‐BDF‐F stands out due to its curved yet coplanar backbone, face‐on orientation, high degree of crystallinity, close π−π stacking distance, the highest electrical conductivity of 3 S cm −1 , the best air stability of electrical conductivity among the series, and an appreciably high power factor. These results demonstrate that theory‐guided design allows for optimizing nonhalogenated n‐type copolymers of low synthetic complexity for thermoelectric applications.